Experimental Investigation of the Effect of Absorber Plate Temperature on Double Slope Inclined Solar Water Desalination Still - Salimizad, Maziar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Solar energy can be used for potable water production from brackish water. In this study the effect of the absorber plate temperature on the inclined solar water desalination having double sloped cover (DS-ISWD) performance was experimentally studied. The DS-ISWD system with net cavity area of 1.5 m2 was constructed and it has two slope glazing; each inclined 250 and four spray jet nozzles were installed at equal intervals within the DS-ISWD. The experience gained form the operation of spray jet solar desalination at the Eastern Mediterranean University, N. Cyprus has revealed the importance of feeding water volume on the system performance. The DS-ISWD system with four jet sprays was tested with different on set temperatures of 40, 45, 50, 55, 60o C in spring (April). The maximum daily yield achieved was 3.85 kg/day m2 when the absorber plate temperature was kept at 55oC. The fresh water yield at 40, 45, 50, 55, and 60oC absorber plate temperatures were 3.6, 3.71, 3.72, 3.85 and 3.68 kg/day m2 respectively. It was observed that when the onset temperature was set 65oC the pump was not in operation after 14:00 hrs. This indicates that the absorber plate temperature was less than 65oC so the system stops generating fresh water after 14:00 hrs. Therefore, the 65 oC plate temperature was ignored in spring tests. The daily average efficiency of DS-ISWD system was observed to be 33.8% for 55oC set-point temperature. The effect of continuous water spraying on the DS-ISWD productivity was also examined. When the absorber plate was at 40oC the pump operated continuously i.e., the feedwater was continuous. The experiments were also conducted in July and the optimum absorber temperature was found to be 65oC with 4.2 kg/day m2 of fresh water production. At 60oC the pump operated continuously and the fresh water production was 5% less than the optimum whereas, the production was decreased by 5% when the absorber plate was at 70oC. From the obtained results it can be concluded that the performance of the DS-ISWD depends on the absorber plate temperature. The DS-ISWD performance also depends on the solar insolation, feedwater temperature, sprayed water size and other climatic parameters. Keywords: Potable water, inclined solar water desalination, absorber plate temperature, thermal efficiency

ÖZ : Güneş enerjisi tuzlu sudan içme suyu üretimi için kullanılabilir. Bu çalışmada, absorber levha sıcaklığının, eğimli güneş su arıtma (EGSA) sisteminin performansına etkisi deneysel olarak incelenmiştir. Net alanı 1.5 m2 olan 25o eğimli iki cam örtülü EGSA sistemi yapılmıştır; dört püskürtme nozulu EGSA içerisine eşit aralıklarla monte edildi. Doğu Akdeniz Üniversitesi'nde püskürtme başlıkları kullanılarak güneş su arıtımasında kaznılan deneyimlerden giriş suyu hacminin EGSA sistem performansına olan önemi ortaya konmulmuştur. Dört püskürtme nozullu EGSA sistemi ilkbaharda (Nisan) absorber plakası ayarlanan farklı sıcaklıklarda 40, 45, 50, 55, 60°C pompa çalıştırılarak test edildi. Maksimum günlük verim plaka sıcaklığı 55oC olduğu günde 3.85 kg/gün m2 olarak elde edildi. Absorber plaka sıcaklıkları 40, 45, 50, 55, ve 60oC ye ayarlandığı zaman arıtılmış su üretimi sırasıyla 3.6, 3.71, 3.72, 3.85 ve 3.68 kg/gün m2 idi. Absorber sıcaklığı 65oC ayarlandığında pompanın saat 14:00 ten sonra çalışmadığı ve su arıtması olmadığı gözlemlendi, bunun nedeni absorber levha sıcaklığının saat ikiden sonra 65oC az olmasıdır. Bu nedenle, 65oC levha sıcaklığı ilkbahardaki testlerde göz ardı edildi. EGSA sistemin 55°C levha sıcaklığındaki ortalama günlük verimliliği %33.8 olduğu görülmüştür. Sürekli su püskürtmenin EGSA üretimine etkisi incelendi. Absorber levha sıcaklığı 40oC ayarlandığı zaman pompanın sürekli çalıştığı gözlemlendi, yani giriş suyu süreklidir. Deneyler Temmuz ayında da yapıldı ve optimum levha sıcaklığı 65oC olup elde edilen günlük tatlı su 4.2 kg/gün m2 dir. 60oC levha sıcaklık ayarında pompa sürekli çalıştı ve üretim optimum üretimden %5 daha azdı, absorber levha sıcaklığı 70oC ayarlandığında üretimin optimuma göre %5 azaldı. Elde edilen sonuçlara göre, EGSA nın performansı absorber levha sıcaklığına, bağlı olduğu sonucuna varılabilir. EGSA nın performansı aynı zamanda güneş radyasyonuna, giriş suyunun sıcaklığına, püskürtülen su damlalarının büyüklüğüne ve diğer iklim a parametrelerine de bağlıdır. AnahtarKalimeler: İçilebilir su, eğimli güneş su arıtma, absorber levha sıcaklığı, ısıl verimlilik.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2014. Co-Supervisor: Assoc. Prof. Dr. Mustafa İlkan, Supervisor: Prof. Dr. Fuat Egelioğlu.
Keywords: Mechanical Engineering; Saline water conversion - Solar energy - Desalination of water; Heat engineering; Potable water; inclined solar water desalination; absorber plate temperature; thermal efficiency